DEVELOPMENT OF A PREDICTIVE MODEL FOR ENHANCED GAS RECOVERY BY CO2 HUFF-N-PUFF INJECTION IN DEPLETED CARBONATE GAS RESERVOIRS - PRATAMA, EDO (2018)
Injecting CO2 with huff-n-puff process is becoming an efficient technique to overcome some productivity damage and enhanced gas recovery in depleted gas reservoirs. Several numerical simulations are required to estimate the gas recovery factor obtained from CO2 huff-n-puff injection. However, numerical simulations are very expensive and time-consuming processes.